2020
DOI: 10.1515/med-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA FGF12-AS2 suppresses the tumorigenesis of NSCLC via sponging miR-188-3p

Abstract: BackgroundNon-small-cell lung carcinoma (NSCLC) seriously threatens the health of human beings. Aberrant expression of lncRNAs has been confirmed to be related with the progression of multiple malignant tumors, including NSCLC. LncRNA FGF12-AS2 has been considered to be upregulated in NSCLC. However, the mechanism by which FGF12-AS2 promotes the tumorigenesis of NSCLC remains elusive.MethodsGene and protein expressions in NSCLC cells were measured by q-PCR and western blot, respectively. CCK-8 and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In the previous studies, NPSR1 ‐ AS1 had been reported as the poor prognosis markers for LUAD 26 ; SATB2 ‐ AS1 could be broadly involved in multiple cancer development 27 , 28 , 29 ; FGF12 ‐ AS2 may be served as a potential target for the treatment of non‐small‐cell lung carcinoma. 30 The evidence further highlighted the PR‐lncRNA signature might exert an essential contribution for LUAD processes and have the potential clinical utility.…”
Section: Resultsmentioning
confidence: 93%
“…In the previous studies, NPSR1 ‐ AS1 had been reported as the poor prognosis markers for LUAD 26 ; SATB2 ‐ AS1 could be broadly involved in multiple cancer development 27 , 28 , 29 ; FGF12 ‐ AS2 may be served as a potential target for the treatment of non‐small‐cell lung carcinoma. 30 The evidence further highlighted the PR‐lncRNA signature might exert an essential contribution for LUAD processes and have the potential clinical utility.…”
Section: Resultsmentioning
confidence: 93%
“…Besides, lncRNA insulin growth factor 2 antisense(IGF2AS) is not only an imprinted gene in Wilms tumors involved in the transcription and translation of a variety of proteins but also a low-expressing lncRNA in NSCLC tissues, which is closely related to the overall survival of patients and a potent inhibitor to the migration of NSCLC cells [39]. Unlike mouse IGF-2AS, human IGF-2AS likely encodes a putative peptide consisting of 273 amino acids [40,41]. IGF-2AS transcripts are mainly present in the cytoplasm and are associated with polysomes, suggesting that the mechanism by which IGF-2AS is involved in tumor progression may be related to the regulation of protein translation [40,41].…”
Section: Lncrna Related To Nsclc Treatmentmentioning
confidence: 99%
“…Unlike mouse IGF-2AS, human IGF-2AS likely encodes a putative peptide consisting of 273 amino acids [40,41]. IGF-2AS transcripts are mainly present in the cytoplasm and are associated with polysomes, suggesting that the mechanism by which IGF-2AS is involved in tumor progression may be related to the regulation of protein translation [40,41].…”
Section: Lncrna Related To Nsclc Treatmentmentioning
confidence: 99%
“…Several of these studies have also reported altered miR-188-3p expression in various human cancers, including gastric cancer[ 12 - 22 ]. For example, miR-183-3p expression was reduced in non-small cell lung cancer vs. normal tissues, whereas miR-188-3p overexpression inhibited tumor cell proliferation and colony formation[ 14 , 16 ]. MiR-183-3p expression was also reduced in human hepatocellular carcinoma compared to normal tissues.…”
Section: Introductionmentioning
confidence: 99%